Determination of Some Characteristics of Traditional Beyşehir Tarhana Production with Poppy Seed Substitution - Şüheda Atar; Bahri Özsisli (Turkish Journal of Agriculture: Food Science and Technology)
In this study, poppy seed, which is rich in vegetable oil and protein, was added to the traditional Beyşehir tarhana instead of wheat batter. It was aimed to develop a new product and to open a new field for the use poppy seeds. The physical, chemical and sensory features of Beyşehir tarhana that was made with poppy seeds, were analysed. Results of the study; humidity is 6.75% to 7.94%; as his %2.75 to %3.66; salt 1.66% to 1.44%; protein 16.92% to 25.71%; oil 11.99% to 24.03%; pH 4.56 to 5.56; acidity 16.43% to 14.59%; energy 423.13 kcal/100g to 480.36 kcal/100g; carbohydrates 61.9% to 40.3%; were found in these amounts, and they are important. Generally, we see that, most of the people liked the taste of the tarhana sample made with 10% poppy seeds so it has the most points. However, the least liked one was the tarhana sample made with %20 poppy seeds and it has the least points. End of the study, it was observed that the addition of poppy seeds to Beyşehir tarhana affected the chemical, physical and sensory qualities of tarhana positively and it was okay with the standards. (Anonymous, 2004) It was determined that the percentage of poppy seeds suitable for tarhana production was 5% and 10%.